(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the different causes of mortality in children and to identify the risk factors associated with mortality. Study Design: Descriptive Study. Place and Duration of Study: This study was conducted in Department of Pediatric unit- IAbbasiShaheed Hospital from April 2010 to March 2011. Materials and Methods: All those infants and children who expired in unit I of Abbasi Shaheed Hospital were included. A previously prepared Performa was filled. The indicators studied were age, sex, total duration of hospitalization, total duration of illness and diagnosis of each infant and child, nutritional status and immunization status of all the children Results: Out of 3420 patients 157 children expired .out of 3420 admitted patients 1789 were males and 1631 were females. Most of the children admitted were below the age of five years. 64 children expiredwithin first 24 hours of admission. 56% were malnourished and 63% were either not immunized or had received only partial immunization. Infectious diseases wereresponsible for67 % of all deaths. Malnutrition, non-immunization, late referrals were the risk factors identified. Conclusion: In this study mortality was found to be 4.59 % and the risk factors identified were similar to other studies conducted in Pakistan and other third world countries. For the good management of patients and to decrease mortality it is suggested that awareness should be made in General practitioners,other health workers andgeneral public for early referrals. Vaccination and malnutrition were major risk factors contributing to death effective strategies are recommended like community based health education campaigns.